prevalence of Metabolic Syndrome in Type 2 Diabetic Patients in Baghdad Teaching Hospital - Alazawi, Omar F.; Allawi, Ali A. Dyab; Saleh, Saleh A. (Journal of the Faculty of Medicine Baghdad, 2013)
Summary: Background: There is an epidemic of several non communicable diseases and metabolic abnormalities in humans including hypertension, obesity, hyperlipidemia, low high density lipoprotein cholesterol, microalbuminurea, and insulin resistance. These diseases and metabolic abnormalities have been collectively classified as metabolic syndrome and are closely associated with type 2 diabetes and other health problems including death. objectives: To investigate the prevalence of metabolic syndrome among type 2 diabetic patients in Baghdad teaching hospital,the frequency, and distribution of risk factors according to gender groups in our studied patients with metabolic syndrome in order to have an idea of the commonest possibly treated and prevented risk factors to decrease morbidity and mortality of metabolic syndrome. Patients and methods: A cross sectional study was done during the period 1st March 2011 till the 1st of March 2012, a sample of 220 patients with diabetes mellitus who accepted to take part in this study was recruited. All patients were subjected to clinical examination and laboratory tests according to the updated ATP111 criteria, in which we measured blood pressure,waist circumference, fasting blood sugar, fasting high density lipoprotein level and fasting triglyceride level, these data were analyzed by Statistical package for social science version 18. Results: There were 220 patients with mean age of (54.52± 9.5), male to female ratio 1.4, metabolic syndrome was present in 41.8% (92) and 58.2% (128) had no metabolic syndrome . The frequency of positive risk factors in association with metabolic syndrome were, for the waist circumference 114 patients (51.8%), high triglyceride level 65 patients (25.5%), low high density lipoprotein level 10 patients (4.5%), hypertension ≥ 130/85 mmHg 117 patients(53.15%) and fasting blood sugar 220 patients (100%). Conclusions: The study showed that metabolic syndrome prevalence still an important factor for the morbidity and mortality of Iraqi patient in spite of its low prevalence compared to other similar studies. Key Words: metabolic syndrome,type 2 diabetes mellitus.